Changes in gut microbiota in peruvian cattle genetic nucleus by breed and correlations with beef quality - Quilcate Pairazamán, Carlos Enrique; Estrada Cañari, Richard; Romero Avila, Yolanda Madelein; Rojas Cruz, Diorman; Mamani Chullo, Rolando; Hañari Quispe, Renán Dilton; Aliaga, Mery; Galindo, Walter; Vásquez, Héctor V.; Maicelo, Jorge L.; Arbizu, Carlos I. (MDPI, 2024)
This study evaluated the gut microbiota and meat quality traits in 11 healthy female cattle from the Huaral region of Peru, including 5 Angus, 3 Braunvieh, and 3 F1 Simmental × Braunvieh. All cattle were 18 months old and maintained on a consistent lifelong diet. Meat quality traits, including loin area, fat thickness, muscle depth, and marbling, were assessed in vivo using ultrasonography. Fecal samples were collected for microbiota analysis, and DNA was extracted for 16S and 18S rRNA sequencing to characterize bacterial, fungal, and protist communities. Significant correlations were observed between microbial genera and meat traits: Christensenellaceae R-7 and Alistipes were positively associated with marbling and muscle area, while Rikenellaceae RC9 showed a negative correlation with fat thickness. Among fungi, Candida positively correlated with marbling, while Trichosporon was negatively associated with muscle depth. For protists, Entodinium negatively correlated with fat thickness and marbling. Alpha diversity varied by breed, with Angus showing greater bacterial diversity, and beta diversity analyses indicated a strong breed influence on microbial composition. These findings suggest that microbial composition, shaped by breed and dietary consistency, could serve as an indicator of meat quality, offering insights into gut microbiota’s role in optimizing cattle production.